2017
DOI: 10.3389/fpsyg.2017.02118
|View full text |Cite
|
Sign up to set email alerts
|

Processing Relative Clause Extractions in Swedish

Abstract: Relative clauses are considered strong islands for extraction across languages. Swedish comprises a well-known exception, allegedly allowing extraction from relative clauses (RCE), raising the possibility that island constraints may be subject to “deep variation” between languages. One alternative is that such exceptions are only illusory and represent “surface variation” attributable to independently motivated syntactic properties. Yet, to date, no surface account has proven tenable for Swedish RCEs. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…According to the surface variation approach, seemingly acceptable violations of island constraints are only apparent exceptions: Island constraints are universal and inviolable, and exceptions reflect different underlying syntactic representations that only look similar on the surface (see for example Kush & Lindahl 2011, Kush et al 2013, Sichel 2018). Tutunjian et al (2017) found that extraction from RCs in Swedish was processed in a different way than strong islands and suggest that this correlates with their apparent acceptability in this language. Tutunjian et al interpret their results as being compatible with a surface (not deep) variation approach, as they view extraction from RCs as constituting a weak island, but an island nonetheless.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…According to the surface variation approach, seemingly acceptable violations of island constraints are only apparent exceptions: Island constraints are universal and inviolable, and exceptions reflect different underlying syntactic representations that only look similar on the surface (see for example Kush & Lindahl 2011, Kush et al 2013, Sichel 2018). Tutunjian et al (2017) found that extraction from RCs in Swedish was processed in a different way than strong islands and suggest that this correlates with their apparent acceptability in this language. Tutunjian et al interpret their results as being compatible with a surface (not deep) variation approach, as they view extraction from RCs as constituting a weak island, but an island nonetheless.…”
Section: Discussionmentioning
confidence: 94%
“…Tutunjian et al. (2017) found that extraction from RCs in Swedish was processed in a different way than strong islands and suggest that this correlates with their apparent acceptability in this language. Tutunjian et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) b. Danish: Diffi cult to process The option of cP-recursion may not be available in relation to all types of island constructions (adjunct islands, relative clauses, complex NPs, subject islands, whether-islands, etc. ), as there appears to be some variation in the acceptability of extractions from these domains within and across the Mainland Scandinavian languages (Kush, Lohndal & Sprouse 2018;Kush, Lohndal & Sprouse 2019;Tutunjian et al 2017). 2 Interestingly, however, 2 As explained in the introduction, the option in Danish of a recursive functional cP-layer ('little' cP) that provides an extra specifi er position as an escape hatch is available only in subordinate clause types.…”
Section: Discussionmentioning
confidence: 99%